Ethnobotany of Women’s Health Plants in Trimulya Village Sanggau Regency - Astuti, A. Cindy; Syamswisna, Syamswisna; Fajri, Hayatul (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
Women's health care is a very important thing to do. However, not all women's health care is safe because most of it uses products or ingredients that can damage the body. The solution for that problem is to use natural ingredients that come from nature as an alternative to maintain women’s health. The people of Trimulya Village, especially women, still use plants to maintain their health. This research aims to determine the plant species used for women's health and how the plant processed as in Trimulya Village. The research method used is descriptive qualitative, with data collection carried out using structured interviews, observation, and documentation. Based on the research results, 21 plant species are used to maintain women's health in Trimulya Village three of which are rarely found, namely white turmeric (Curcuma zedoaria Roxb), Chinese betel (Peperomia pellucida (L.) Kunth), and lempuyang (Zingiber zerumbet (L.) Roscoe). The most frequently used processing method is by boiling. The plants used by the community are come from their garden or the yard of the house.